General microbiology - Schlegel, Hans G. (Cambridge University Press, 1993)
The revised and expanded edition of Professor Schlegel's well-established textbook is an excellent introduction to microbiology to a wide range of undergraduate students. Although primarily aimed at students of microbiology, it will also be suitable for all life-science undergraduates whose courses include microbiology as a component, whether they are studying botany, zoology, pharmacy, medicine or agriculture as their main subject. By concentrating on the essential aspects of microbiology, the student is unerringly provided with an excellent general overview of microbiology, without becoming distracted by a wealth of unnecessary detail. This new edition brings fully up to date the various advances in the subject, including new species, phylogenetic relationships and novel metabolic pathways, and a greater emphasis on environmental and ecological matters